PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SMK: SYSTEMATIC LITERATURE REVIEW - Habel Wilefri Al Hadad; Nizwardi Jalinus; Ernawati Ernawati; Elfi Tasrif (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study focuses on analyzing the influence of the principal's transformational leadership as an effort to improve teacher performance in Vocational High Schools (SMK). This study uses the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. This study uses narrative synthesis and thematic analysis of twelve national and international scientific articles that are appropriate and relevant to the research topic with a publication period of 2016-2026. The results of the study indicate that transformational leadership has an important role in improving teacher performance driven by four dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These dimensions play a role in improving teacher professionalism, work motivation, work discipline, learning innovation, job satisfaction, and teacher academic productivity. This relationship is strengthened by the presence of mediating variables in the form of work motivation, self-efficacy, emotional intelligence, and learning organization, so that this leadership supports the Teaching Factory (TEFA), digitalization of learning, collaboration between institutions, and graduate work readiness. This study presents a concise and integrated synthesis of the strategic role of transformational leadership carried out by school principals as an effort to improve teacher performance and vocational education in particular in a sustainable manner.